(untitled) (VETERINARIA, 2020)
The antimicrobial activity of two antimicrobial peptides, cecropin A and polymyxin B against different bacterial pathogens associated with bacterial dermatosepticemia, a fatal bacterial infectious disease of frogs was investigated. The peptides were tested in serial of concentrations (100-0.19 µg/ml) for growth inhibition of seven pathogens: Aeromonas hydrophila, Chryseobacterium meningosepticum, Citrobacter freundii, Klebsiella pneumoniae, Pseudomonas aeruginosa, Proteus mirabilis and Serratia liquefaciens. Their antimicrobial activity was compared with that of two antimicrobial peptides from frog skin, magainin 2 and aurein 2.1. Both cecropin A and polymyxin B, completely inhibited the growth of three pathogens: C. freundii, K. pneumoniae and P. aeruginosa at a concentration some sixteen times less than two skin peptides. Furthermore, cecropin A inhibited the growth of three pathogens resistant to the two skin peptides, A. hydrophila, C. meningosepticum and P. mirabilis. Polymyxin B also inhibited the growth of three pathogens resistant to the skin peptides, A. hydrophila, C. meningosepticum and S. liquefaciens. Cecropin A and polymyxin B have marked antibacterial activity against different frog bacterial pathogens indicating potential for therapeutic measures.